Quantification of green carbon changes in relation with LULC changes using remote sensing - GIS technology in Kuantan river basin - Syarifuddin, Misbari; Anis Nadira, Asha’ari; Efiong Eyo, Etim (Semarak Ilmu Publishing, 2024)
Land use land cover changes (LULCC) is a process that is influenced by anthropogenic effect. The growth of population is increasing, which leads to a demand on metropolitan regions. However, these urbanization and development are significant contributors to the expansion of LULCC conflict at an alarming rate to fulfil the human needs. LULCC has derived huge effects towards the environment which is biomass and green carbon changes. LULCC has caused vegetation covers of the land being degraded which reducing the total biomass of the area and implemented to that, the carbon stock for the area is increasing causing climate change and global warming. Therefore, the estimation of total carbon is important to be conducted. The existing map of LULCC is not update, the inventories information about the total carbon in Kuantan is not well covered, people in this region are lack of awareness about the harmful of carbon in the air, and conventional method is hard to be applied for carbon estimation are the problems that have derived for this study to be conducted. This study is focused on quantification of total carbon in Kuantan district to raise the awareness towards the local communities about the danger of high amount of carbon. The objective of this study is to classify LULC types in Kuantan district using geospatial artificial intelligent (GeoAI) approach on satellite images, to relate soil types, vegetation index and satellite – based total biomass in Kuantan River basin and to map green carbon changes in Kuantan based on quantified biomass using remote sensing – GIS technology. Therefore, this study is focused on Kuantan district to quantify the total biomass and carbon in this area by using selected multispectral satellites images with high spatial resolution Landsat 8 OLI, and Landsat 5 TM.